Tasawuf Marketing: Merekonstruksi Brand Love Islami dengan Pendekatan Sufistik - Anwar, Moh Muhlis (Universitas Islam Raden Rahmat, 2025)
Write down your English language (United Kingdom) abstract here. This study explores the dimensions of Islamic brand love through a Sufi approach, aiming to understand how Sufi principles can deepen the relationship between consumers and Shariah-compliant brands. Within the Sufi framework, dimensions of love such as Hulla (friendship), Hawa (passion), Ma’rifa (knowledge), Dzikra (memory), and Ru’ya (vision) are adapted to build a deep emotional and spiritual attachment between consumers and the brand. By integrating Sufi principles into marketing, Shariah-compliant brands can create experiences that not only fulfill emotional needs but also resonate with the spiritual values of consumers. The findings of this study suggest that the Sufi approach can enhance consumer loyalty and satisfaction, offering new insights into brand love in the Islamic context. The study recommends the application of Sufi dimensions in marketing strategies to build more meaningful and sustainable relationships between brands and consumers.